Hubungan Durasi Pembedahan dengan Nyeri Tenggorokan pada Pasien Post General Anestesi Teknik Intubasi Endotracheal Tube di RSI Purwokerto - Ghaihab Dzikir Mufiid Alkatiri; Tophan Heri Wibowo; Ita Apriliyani (Jurnal Kesehatan Amanah, 2025)
Surgery is one of the medical procedures divided into three periods of pre operative, intra operative, and post operative. At least 11% of the global disease burden comes from conditions that can actually be addressed through surgery. Surgical procedures will certainly require anesthesia, one of which is general anesthesia with the Endotracheal Tube (ETT) intubation technique. Endotracheal Tube (ETT) intubation can cause various complications, the most common being postoperative sore throat. One of the risk factors for sore throat after Endotracheal Tube (ETT) intubation is the duration of surgery. This research is a quantitative study with a descriptive correlational design and a cross-sectional approach. The sample in this study consisted of 30 patients undergoing surgery with general anesthesia using the Endotracheal Tube (ETT) intubation technique, determined by quota sampling. The research instruments used were a clock to measure the duration of surgery and an observation sheet containing the measurement of sore throat level using the Numeric Rating Scale (NRS). Data analysis in this study included univariate and bivariate analyses, with the latter tested using the Spearman rank test. The results of the Spearman rank test between the variables of surgical duration and postoperative sore throat in general anesthesia with the Endotracheal Tube (ETT) intubation technique showed a p = 0.000 and an r = 0.912, which means that the two variables have a significant and positive relationship in line with a very strong correlation strength. This indicates that the longer the duration of surgery, the higher the postoperative sore throat scale in general anesthesia with the Endotracheal Tube (ETT) intubation technique.